Natural Metal/Oxides for Catalytic Oxidation of Persistent Organic Pollutants (POPs) in Contaminated Water and Soil - Yao, ZhengXin (Curtin University, 2021)
This study proposed an effective strategy by utilizing natural minerals consisting of transition metal elements as the substitute for conventional synthetic catalysts in PMS activation to decompose organic pollutants in situ, which enables the manufactory to markedly reduce the processing cost, contributing to the industrial application of natural minerals in environment remediation technology.